Self-rated health among older adults: a cross-national comparison - Bardage, Carola (Eur J Ageing, 2005)
Self-rated health (SRH) may have different implications in various social and cultural settings. However, few studies are available concerning SRH among older persons across countries. The aim of this study was to analyse whether there are cross-national differences in the association between status characteristics, several diseases common among older persons, activities of daily living (ADL), and SRH. The study base was the Comparison of Longitudinal European Studies on Aging (CLESA), which includes data from six population-based studies on aging conducted in Finland, Israel, Italy, The Netherlands, Spain and Sweden. The study population comprised 5,629 persons, with participants from all countries except Italy. Logistic regression analyses were used to assess the relationship between status characteristics, health conditions, ADL and SRH. To examine whether the association among status characteristics, health conditions, ADL and outcome differed across the CLESA countries, interaction terms defined as “variable*country” were considered separately for each variable. Regression analyses revealed that sex, education, lifetime occupation, heart disease and respiratory disease were differently distributed across countries. Among homogeneous factors, marital status (OR=1.21), hypertension (OR=1.41), stroke (OR=1.67), diabetes (OR=2.15), cancer (OR=1.47), musculoskeletal diseases (OR=2.44), and ADL (OR=2.72) turned out to be significantly associated with fair or poor SRH. The results indicate that there are differences in self-ratings of health across countries. These differences cannot be explained entirely by status characteristics, self-reported diseases or functional ability. However, an important finding was that in all countries most of the indicators of medical and functional health were homogeneously associated with SRH.